OPTIMIZATION OF pH VALUE AND GEL VISCOSITY IN PORANG TUBER CAPSULE SHELL FORMULATION - Maulana, Riza; Muhtadi; Suhendi, Andi; Prasetya, Farid Adi; Harimurti, Sabtanti; Hamzah, Hasyrul (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
The porang tuber contains glucomannan compounds that can expand into a gel so that it has the potential to be used as the main ingredient of capsule shells. This research aims to optimize the pH and viscosity values that can affect the consistency of the capsule shell produced. The method used in the manufacture of capsule shells is the dipping pen method, while the optimization method carried out is trial and error by making 3 formulas by combining glycerin and PEG 400. The results obtained by the gel mass formed by the glycerin-PEG 400 gelling agent have a viscosity value of 586.67 dPas and a pH value of 6.02 can provide a gel mass that is easy to mold capsule shells and obtain capsule shells with elastic characters. The results indicate optimal viscosity and pH values to obtain a gel mass that is easy to mold capsule shells with good organoleptic characteristics. Keywords: Glucomannan, pH, viscosity, capsule shell.